Automatic management modern consumer - regulate are decision question of providing frequency stability in of union OES of Ukraine, with demant of UCTE - Dubovskoy S.V.; Lenchevsky Ye.A.; Martinenko S.A. (General Energy Institute of the National Academy of Sciences of Ukraine, 2009)
Questions are considered elucidate not effective use in OES of Ukraine exist methode regulate of frequency, and also exist project insert constant talk (WPT) at decision are considered of providing of energosystems OES of Ukraine with UCTE. The new analytical decision are considered of management of new netraditional method of providing of stability of frequency in OES of Ukraine. Carru out theory investication for decision are considered.